Estrategias de marketing digital en El Minimarket Joha de la ciudad de Babahoyo, periodo 2022. - Contreras Barreno, Lexy Victoria (2023)
The present case study was carried out in the city of Babahoyo in the Joha Minimarket dedicated to the sale of essential products. To develop this research it was decided to analyze the current situation of this venture. During the analysis of this research work, it was determined that this minimarket does not have a digital marketing strategy plan, since it is very necessary and which is considered very important for local positioning in the city of Babahoyo. For this research, an interview was conducted with the owner of the establishment where it was discovered that he has problems when promoting his minimarket and publicizing the products he offers due to the lack of knowledge in the marketing area, which makes it difficult to increase sales in the establishment.